FAIR AND EQUITABLE TREATMENT STANDARD IN THE INTERNATIONAL INVESTMENT AGREEMENTS - Sefriani, Sefriani (Yustisia, 2018)
In the last five years, the number of investors who suit against host state in the international arbitration forum increased significantly. Almost all lawsuits used fair and equitable treatment (FET) standard which has been violated by the host state. Most of international investment agreements including those that were made by Indonesia contain FET standard clauses. However, there are no definitions related to this standard. This condition potentially raises a very wide interpretation of the standard. The problem formulations in this article are how the history of FET is, where its position in international investment law is and what elements of FET standard are. The results show that the FET standard has existed since Havana Charter followed by various FCN, BIT and other international investment agreements. FET standard can be categorized as customary international, legally binding on all countries regardless their national law. Although there is no universal approval regarding the scope of FET standard, the writings which have been published and the arbitral tribunal decision mentions that those elements are legitimate expectation; due process; denial of justice; rule of law; non- discrimination; transparency; consistency, good faith, and reasonableness.